2015
DOI: 10.14689/ejer.2015.60.1
|View full text |Cite
|
Sign up to set email alerts
|

Turkish Version of the Principals’ Sense of Efficacy Scale: Validity and Reliability Stud

Abstract: Problem Statement: Principals are known as important actors in effective schools. So it is important to know which variables influence principals' success. One of these predictors can be self-efficacy. However, there is very few research about principals' sense of efficacy. Purpose of the Study:The purpose of this research was to test the psychometric properties of the Turkish version of the Principal Sense of Efficacy Scale (PSES-T).Method: Confirmatory and Exploratory factor analysis were conducted in order … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…The Diken research ( 2006) also focused on the views of kindergarten teachers with regards to inclusive education, through the Turkish version of the Opinions Relative to Mainstreaming Scale (TORMS) (Diken, 2004). The results showed that the researched teachers had significantly positive attitudes towards the inclusion of children with mental disabilities.…”
Section: Discussionmentioning
confidence: 99%
“…The Diken research ( 2006) also focused on the views of kindergarten teachers with regards to inclusive education, through the Turkish version of the Opinions Relative to Mainstreaming Scale (TORMS) (Diken, 2004). The results showed that the researched teachers had significantly positive attitudes towards the inclusion of children with mental disabilities.…”
Section: Discussionmentioning
confidence: 99%
“…TSES -Teachers' Sense of Efficacy Scale - (Duffin et al, 2012) shows three areas of teaching effectiveness: (a) classroom management; (b) student engagement; and (c) teaching strategies. Another tool is the PSES -Principals' Sense of Efficacy Scale - (Isik & Derinbay, 2015), which consists of three subscales: effectiveness for management, effectiveness for teaching, and effectiveness for ethical leadership.…”
Section: Measuring Teaching Self-efficacymentioning
confidence: 99%
“…Several studies have examined kindergarten teachers' attitudes and opinions towards inclusion. Study by Diken (2006) also focused on kindergarten teachers' attitudes and opinions towards inclusive education by using the Turkish version of Opinions Relative to Mainstreaming Scale (TORMS) (Diken, 2004). The results showed that the respondents had significantly positive attitudes towards inclusion of children with intellectual disabilities.…”
Section: Theoretical Starting Point Of the Studied Issuementioning
confidence: 99%